Report of Three Cases of AKI Following Weight-Based Gentamicin Prophylaxis for IPP Implantation: Potential Concerns for Patients with Preexisting Conditions - Robert H. Moore; Uzoma A. Anele; Sarah C. Krzastek; Adam P. Klausner; J. Tyler Roseman (Case Reports in Urology)
Despite the known nephrotoxicity of gentamicin, in 2008 the American Urological Association published guidelines recommending single high-dose weight-based gentamicin prophylaxis of 5 mg/kg for procedures involving urologic prostheses. These guidelines are based on the theoretical renal safety and improved antimicrobial activity of a single large dose of gentamicin. However, the risk of nephrotoxicity after weight-based gentamicin prophylaxis specifically in penile prosthetic surgery has never been established with evidence-based studies. This is of special concern in light of the known high rates of preexisting conditions in this specific population. Therefore, in order to expose potential safety issues, we present three cases of postoperative acute kidney injury following weight-based gentamicin prophylaxis after implantation of inflatable penile prostheses.